THE INTERNATIONAL CRIMINAL COURT'S (ICC) JURISDICTION OVER ISRAEL'S BLOCKADE ON THE GAZA STRIP: EXAMINING THE CRIME OF AGGRESSION - Jannah, Dara Raihatul; Mahfud, Mahfud (Universitas Syiah Kuala, 2023)
This paper thoroughly examines the crime of aggression in the form of the blockade of the Gaza Strip imposed by Israel and the jurisdiction of the International Criminal Court (ICC) over this matter, despite Israel not being a state party to the Rome Statute. The research conducted is based on normative judicial research, utilizing primary and secondary legal resources. The findings of this research highlight the significant impact of the blockade on the Gaza Strip and Israel's violation of Article 8 bis of the Rome Statute, which specifically pertains to the crime of aggression. Israel's actions can be unequivocally categorized as a crime of aggression, as they fulfill the elements outlined in the article defining this crime. It is important to note that the ICC retains jurisdiction over the crime of aggression, even in cases involving non-member states like Israel, through UN Security Council referrals. In light of this, it is imperative for the ICC to take proactive action and prosecute Israel for this crime, serving as the last resort for global justice seekers.